PDK4 Inhibits Cardiac Pyruvate Oxidation in Late Pregnancy. Issue 12 (8th December 2017) - Liu, Laura X.; Rowe, Glenn C.; Yang, Steven; Li, Jian; Damilano, Federico; Chan, Mun Chun; Lu, Wenyun; Jang, Cholsoon; Wada, Shogo; Morley, Michael; Hesse, Michael; Fleischmann, Bernd K.; et al.
Abstract : Rationale: : Pregnancy profoundly alters maternal physiology. The heart hypertrophies during pregnancy, but its metabolic adaptations, are not well understood. Objective: : To determine the mechanisms underlying cardiac substrate use during pregnancy. Methods and Results: : We use here 13 C glucose, 13 C lactate, and 13 C fatty acid tracing analyses to show that hearts in late pregnant mice increase fatty acid uptake and oxidation into the tricarboxylic acid cycle, while reducing glucose and lactate oxidation. Mitochondrial quantity, morphology, and function do not seem altered. Insulin signaling seems intact, and the abundance and localization of the major fatty acid and glucose transporters, CD36 (cluster of differentiation 36) and GLUT4 (glucose transporter type 4), are also unchanged. Rather, we find that the pregnancy hormone progesterone induces PDK4 (pyruvate dehydrogenase kinase 4) in cardiomyocytes and that elevated PDK4 levels in late pregnancy lead to inhibition of PDH (pyruvate dehydrogenase) and pyruvate flux into the tricarboxylic acid cycle. Blocking PDK4 reverses the metabolic changes seen in hearts in late pregnancy. Conclusions: : Taken together, these data indicate that the hormonal environment of late pregnancy promotes metabolic remodeling in the heart at the level of PDH, rather than at the level of insulin signaling. Abstract : Supplemental Digital Content is available in the text.